Fatty Acid Composition and Lipid Profile of Diospyros mespiliformis, Albizia lebbeck, and Caesalpinia pulcherrima Seed Oils from Nigeria - Adewale Adewuyi; Rotimi Ayodele Oderinde (International Journal of Food Science)
The screening of lesser-known underutilized seeds as source of food has been a way of finding solution to food insecurity in developing nations. In this regard, oil as a class of food was extracted from the seeds of Diospyros mespiliformis  (4.72±0.2%), Albizia lebbeck  (6.40±0.60%), and Caesalpinia pulcherrima  (7.2±0.30%). The oils were finally analyzed for their fatty acid composition, lipid classes, fatty acid distribution in the lipid fractions, and molecular speciation of the triacylglycerols, glycolipids, and phospholipids. The fatty acid composition of the oils varied with C18:2 fatty acid being the most dominant in the oils. Neutral lipids were the most abundant lipid class found in the oils while molecular species of the triacylglycerol with equivalent carbon chain number C40 was majorly present in the oils of Diospyros mespiliformis and Caesalpinia pulcherrima. The present study presents lesser-known underutilized seeds as possible sources of food.